Estudo neuroanatômico do éncefalo bovino por ressonância magnética - Bueno, Laís Melicio Cintra [UNESP] (2015)
Magnetic resonance imaging (MRI) has revolutionized veterinary medicine in the field of diagnostic imaging. Technology currently considered as the most sensitive method for the analysis of soft tissues such as the brain, bypassing the other diagnostic methods. This technology is based on nuclear magnetic resonance phenomenon that occurs when atomic nuclei with magnetic properties present in the body of humans and animals are subjected to an intense magnetic field. Its advantages in the production of brain images are noninvasive, is characterized by high resolution, high contrast, two-dimensional plane, grayscale, produces less artifacts and does not use ionizing formats of electromagnetic energy. Presents no risk to the patient and proven professionals submitted to the examination. Although MRI is the preferred technique to examine the brain, this information is scarce when related brain anatomical features in domestic ruminants. The purpose of this study is to describe normal bovine brain neuroanatomy (Bos taurus domesticus) order correlations with normal magnetic resonance imaging findings. This research is of importance because, normal neuroanatomical definition will provide accurate diagnosis of different diseases traumatic, vascular, infectious, degenerative or neoplastic, among other. Brains were carefully extracted and fixed for conventional anatomical cuts. Transverse and sagittal MRI were obtained from two fresh heads of adult cattle at 0.25T ESAOTE Vet-MR GRANDE device through the coil C-shaped coil in the sequences performed in the transverse plane T1 and T2 sagittal, T1 and T2 and the plan dorsal. After the acquisition, images were transferred in DICON format for Synapse® PACS application and analyzed by an observer at ClearCanvas Workstation program. The most clinical interest neuroanatomical structures were set according to the methodology of Yokoshi & Rohen and named after neuroanatomy texts